2021
DOI: 10.17977/um031v7i12021p53-56
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kebutuhan dan Masalah Pembelajaran Jarak Jauh pada Anak Berkebutuhan Khusus di Masa Pandemi Covid-19

Abstract: Penelitian inibertujuan untuk mengali informasi tentang kebutuhan dan masalah yang timbul selama pembelajaran jarak jauh pada Anak Berkebutuhan Khusus di masa pandemi Covid-19. Metode penelitian menggunakan kualitatif deskriptif dengan pendekatan case study. Dengan jumlah responden 220 guru Sekolah inklusi dan Sekolah Luar Biasa di Indonesia. Penyebaran instrument melalui google form yang kemudian dianalisis menggunkan SPSS. Hasil penelitian yang didapatkan temuan antara lain; 1) kendala terbesar yang dialami … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Studies in the early days of the pandemic found various problems experienced by teachers in special schools. For instance, teachers have problems with internet access, unpreparedness for using technology, and difficulties in planning and choosing adaptive learning models and media for students with special needs [13]. Also, teachers face challenges in educating children with special needs in distance learning.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the early days of the pandemic found various problems experienced by teachers in special schools. For instance, teachers have problems with internet access, unpreparedness for using technology, and difficulties in planning and choosing adaptive learning models and media for students with special needs [13]. Also, teachers face challenges in educating children with special needs in distance learning.…”
Section: Introductionmentioning
confidence: 99%
“…Another concern that arises is the presence of teachers to monitor the learning process and the learning outcomes, which results in the lack of feedback on students' understanding of the subject and students' development monitoring. As a result, learning ineff ectiveness reaches 86% since teachers only use the Whatsapp platform to deliver assignments and learning materials (Supriyadi & Wiliyanto, 2021). In addition, 84% of respondents experience certain diffi culties in selforganization, time planning, and independent teaching material management (Denisova, Lekhanova, & Gudina, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Online learning presents its challenges for accompanying teachers in inclusive schools because students with special needs are among the groups most vulnerable to educational decline if distance learning is applied. As stated by (Supriyadi & Wiliyanto, 2021) the biggest obstacle experienced by teachers in distance learning for Children with Special Needs is the unstable internet network and the application of distance learning for Children with Special Needs (ABK) is very ineffective.…”
Section: Introductionmentioning
confidence: 99%